Does One Size Fit All? Exploring the Contribution of Text features, Text content, and Grade of Use on Comprehension. Issue 1 (11th December 2020) - Anne E. Mesmer, Heidi; Hiebert, Elfrieda H.; Cunningham, James W.; Kapania, Madhu
Abstract: Readability systems have once more become prominent in policy and practice because of recommendations in the Common Core State Standards. This study revisited two features of current text analysis (readability) systems: their generalizability to all grade levels and to all content areas. A database that encompassed texts across the grade bands and content areas and included aggregate comprehension performance on the texts was used to: (a) describe how the text features (i.e., word frequency, word length, sentence length) varied at different grade levels and within different subject areas and (b) examine if the prediction of comprehension with the text features was moderated by the grade or content area of the text. Results indicated that texts did having differing levels of various word features along both grade and content lines especially in the area of sentence length. In addition, content and grade moderated the relationship between sentence length and comprehension.